2009
DOI: 10.1128/aac.01556-08
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Advanced Invasive Pulmonary Aspergillosis in Transiently Neutropenic Rats Using Human Pharmacokinetic Equivalent Doses of Voriconazole and Anidulafungin

Abstract: At present, voriconazole (VOR) is the drug of first choice for treating invasive pulmonary aspergillosis (IPA).However, particularly in advanced stages of disease and in the severely immunocompromised host, the mortality remains substantial. The combination of VOR with an echinocandin may improve the therapeutic outcome. We investigate here whether combining VOR and anidulafungin (ANI) in advanced IPA in transiently neutropenic rats results in a higher therapeutic efficacy. Since VOR is metabolized more rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…In humans, the AUC after a standard dose is slightly over 100 mg · h/liter (28,29). Andes et al found that a fAUC 0-24 /MEC value of 100 was required to result in a static effect in a Candida infection model (27).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the AUC after a standard dose is slightly over 100 mg · h/liter (28,29). Andes et al found that a fAUC 0-24 /MEC value of 100 was required to result in a static effect in a Candida infection model (27).…”
Section: Discussionmentioning
confidence: 99%
“…The posaconazole static dose for this combination was reduced by almost 13-fold compared to that for monotherapy, which is both highly statistically significant and, one might expect, clinically important (P Յ 0.001). Previous in vivo studies have demonstrated similar enhanced effects with voriconazole and each of the three licensed echinocandins (52)(53)(54)(55)(56)(57), although this is the first to utilize posaconazole and to examine the results from a pharmacodynamic perspective.…”
Section: ͼ40mentioning
confidence: 99%
“…In contrast, the good results obtained with the therapy were not accompanied by a decrease in galactomannan serum levels. This fact was also observed in disseminated and pulmonary murine infections by A. fumigatus (1,10,14,15). It has been suggested that due to their fungistatic activity, the echinocandins are not able to reduce galactomannan levels in serum, since this phenomenon was not observed in the treatment of aspergillosis with fungicidal drugs, like azoles (1).…”
mentioning
confidence: 75%